THE INFLUENCE OF THE CONDITION OF AIRSIDE PARAMETER FENCE FACILITIES ON FLIGHT SECURITY AND SAFETY AT KUPANG EL TARI INTERNATIONAL AIRPORT - Alvariz, Alvin; Hariyanto, Didi; Musadek, Ahmad (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2024)
In addressing the evolving issues, it is important to have effective and standardized security measures in place in the face of increasing security challenges to protect airport facilities and prevent threats to aviation safety and security. Airside security facilities such as perimeter fences with conditions in accordance with Ministerial Regulation 167/2015 update of Ministerial Regulation 33/2015 are required to demarcate airport areas and protect airside airport activities such as aircraft takeoffs and landings. A correlational method with a quantitative approach was used in this study. The data of this study came from observation data and questionnaire distribution. Respondents in this study were Aviation Security (AVSEC) and Apron Movement Control (AMC) personnel. From the respondents’ responses, the data will be processed using the IBM SPSS Statistic 27 For Windows application program. The results of the calculation state that the condition of the parameter fence facility (variable X) correlates with aviation security and safety (variable Y). The condition of the parameter fence facilities at El Tari Kupang International Airport is stated to be still not in accordance with Ministerial Regulation 167/2015 update of Ministerial Regulation 33/2015 which can be seen on the observation sheet. While the strength of the relationship between the condition of the parameter fence facilities and aviation security and safety is proven by the hypothesis correlation test with the help of the IBM SPSS Statistic 27 For Windows application program with the result of 0.735 which means a strong relationship.